The accumulation of foreign reserves - Georges Pineau; Ettore Dorrucci (European Central Bank (ECB), 2006)
In a number of countries, especially emerging market economies, the public sector has in recent years been accumulating sizeable cross-border financial assets, mainly in the form of official foreign exchange reserves. World reserves have risen from USD 1.2 trillion in January 1995 to above USD 4 trillion in September 2005, growing particularly rapidly since 2002. This paper investigates the features, drivers, risks and costs of such recent reserve accumulation, as well as the other uses that certain countries have been making of their accumulated foreign assets. The main trends in central bank reserve management are also reviewed. Finally, the paper provides some evidence for the impact of reserve accumulation on yields and asset prices.
Keywords: 330; Foreign exchange reserves; exchange rates; emerging market economies.; Währungsreserven; Währungsmanagement; Welt